Retrospective comparison of hydrostatic and pneumatic reduction of childhood intussusception at Red Cross Children's Hospital (1989-1997) - De Villiers, Jean Pierre (Division of Radiology, 2018)
In accordance with consensus of the current literature, we have been using pneumatic reduction by preference at Red Cross Children's Hospital (RCCH) since the early 1990's. The aim of this study is to evaluate the results of our experience since 1989 as we have gradually moved from the hydrostatic method to the pneumatic method. This study will present results of 100 cases seen over a seven year period at the Red Cross Children's Hospital. The results of the respective reduction techniques will be discussed with special attention on complication rates, efficiency and cost implications.